ANALISIS KINERJA KEUANGAN PADA KOPERASI KARYAWAN SEJAHTERA ABADI PT BANK PAPUA CABANG TIMIKA - Fitriawati Fitriawati; Longginus Gelatan (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2021)
The main purpose of this study is to find out how the financial performance of the PT Bank Papua Abadi Sejahtera Abadi Cooperative is based on net profit margin, economic profitability and own capital profitability. This study uses descriptive research is a method of solving a problem stage that describes the state of the company in the form of a particular subject or object. The instrument used is the net profit margin ratio shows the company's efficiency by looking at profits, economic profitability measures the company's ability to generate profits and the profitability of its own capital shows the company's ability with its own capital to generate profits. The results of this study indicate that the Financial Performance Analysis of the PT Bank Papua Abadi Sejahtera Abadi Employee Cooperative by using the ratio of net profit margin, economic profitability, own capital profitability can be said to be